Les écrivains témoins du peuple - Fourastié, Jean (1907-1990); Fourastié, Françoise
Sur la couv. : "textes de : Glaber, Chrétien de Troyes, Rutebeuf, Le Bourgeois de Paris, Ambroise Paré, St Vincent de Paul, La Bruyère, La Fontaine, Vauban, Marquis d'Argenson, Arthur Young, Sébastien Mercier, Capitaine Coignet, Nicolas Lachaux, Michelet, Martin Nadaud, George Sand, Villermé, Frédéric Le Play, Lamartine, Agricole Perdiguier, Victor Hugo, Bruno, Comtesse de Ségur, J. H. Fabre, Émile Zola, Alphonse Daudet, Eugène Leroy, Émile Guillaumin"